Agrotourism for Sustainable Rural Development: A Case Study of Garut Selatan - Nyanjang Abdul Basit; Muhamad Yusup (Indonesian Research of Sustainability Management, Business, & Administration (IRHAMNA), 2025)
Background: Rural communities face economic challenges due to market volatility, climate change, and rural depopulation. Agrotourism has emerged as a strategy for economic diversification, offering rural areas opportunities for sustainable development. However, its implementation varies due to differences in policy support, infrastructure, and community engagement. This study explores the potential of sustainable agrotourism as a driver of rural economic development in Garut Selatan, Indonesia. Methods: A qualitative case study approach was adopted, involving semi-structured interviews with key stakeholders, focus group discussions (FGDs), and policy document analysis. Thematic analysis was conducted to identify patterns, and data triangulation was applied to enhance validity and reliability. Results: The study finds that Garut Selatan possesses strong agricultural and cultural assets that can support agrotourism, including tea plantations, organic farms, and traditional farming practices. Agrotourism has the potential to improve rural livelihoods, create employment, and support environmental sustainability. However, challenges such as inadequate infrastructure, financial constraints, and weak stakeholder coordination hinder its development. Conclusions: Sustainable agrotourism can serve as a key driver of rural economic development if supported by comprehensive policies, improved infrastructure, and capacity-building initiatives. The adoption of the Pentahelix model, integrating academia, business, community, government, and media, is essential for sustainable growth. Implications: These findings provide insights for policymakers, businesses, and local communities to develop agrotourism as a long-term economic strategy while preserving environmental and cultural heritage. Limitations: The study relies on qualitative methods, which may limit generalizability. Future research should incorporate quantitative assessments to measure economic impact and tourist preferences for more comprehensive insights.